Relationship between left ventricular ejection fraction and mortality after myocardial infarction complicated by heart failure or left ventricular dysfunction. (1st December 2018) - Hall, Trygve S.; von Lueder, Thomas G.; Zannad, Faiez; Rossignol, Patrick; Duarte, Kevin; Chouihed, Tahar; Dickstein, Kenneth; Atar, Dan; Agewall, Stefan; Girerd, Nicolas; ,
Abstract: Background: Identifying risk factors for specific modes of death in patients with heart failure (HF) or left ventricular (LV) dysfunction after acute myocardial infarction (MI) may help to avert events. We sought to evaluate LV ejection fraction (LVEF) as a prognosticator of specific death modes. Methods and results: In an individual patient data meta-analysis of four merged trials (CAPRICORN, EPHESUS, OPTIMAAL, and VALIANT), Cox modelling was performed to study the association between baseline LVEF from 19, 740 patients and types of death during follow-up. Over a median follow-up of 707 days 3419 deaths occurred. The distribution pattern for mode of death was similar across categories (LVEF < 25%, LVEF 25–35%, and LVEF > 35%). In multivariable models, the risk of all types of death increased with decreasing LVEF. If compared to LVEF > 35%, LVEF < 25% was associated with a 113% increased risk of sudden death (hazard ratio (HR) 2.13, 95% confidence interval (CI) 1.53–2.98), a 170% increased risk of HF death (HR 2.70, 95% CI 1.83–3.98), a 66% increased risk of other cardiovascular (CV) death (HR 1.66, 95% CI 1.14–2.42), and a 90% increased risk of non CV death (HR 1.90, 95% CI 1.15–3.14). Conclusion: In patients with HF or LV dysfunction after acute MI, low LVEF is a ubiquitous risk marker associated with death regardless of type. The different modes of death are fairly equally represented throughout the categories of LVEF and sudden death remains a significant mode of death also in patients with LVEF > 35%. Highlights: LVEF as a prognosticator of specific death modes is evaluated. The risk of all types of death increased with decreasing LVEF. Different modes of death are fairly equally represented throughout LVEF categories. Sudden death remains a significant mode of death also in patients with LVEF > 35%.